Risk of bleeding in patients undergoing pulmonary procedures on antiplatelet or anticoagulants: A systematic review. (July 2019) - Herman, D.D.; Thomson, C.C.; Brosnhan, S.; Patel, R.; Trosini-Desert, V.; Bilaceroglu, S.; Poston, J.T.; Liberman, M.; Shah, P.L.; Ost, D.E.; Chatterjee, R.; Michaud, G.C.
Abstract: As many as 25% of all patients undergoing invasive pulmonary procedures are receiving at least one antiplatelet or anticoagulant agent. For those undergoing elective procedures, the decision-making process is uncomplicated and the procedure may be postponed until the antiplatelet or anticoagulant agent may be safely held. However, many invasive pulmonary procedures are semi-elective or emergent in nature in which case a risk-benefit calculation and discussion occur between the provider and patient or surrogate decision-maker. Therefore, it is critical for providers to have an awareness of the risk of bleeding complications with different pulmonary procedures on various antiplatelet and anticoagulant agents. This systematic review summarizes the bleeding complications associated with different pulmonary procedures in patients on various antiplatelet or anticoagulant agents in the literature and reveals a paucity of high-quality evidence across a wide spectrum of pulmonary procedures and antiplatelet or anticoagulant agents. The results of this review can help inform providers of the bleeding risk in these patients to aid in the shared decision-making process and risk vs benefit discussion. Highlights: Up to 25% of patients undergoing pulmonary procedures are on antithrombotic therapy. Pre-procedural evaluation includes patient and procedural bleeding risk assessment. Only transbronchial biopsy is informed by large, albeit uncontrolled, cohort studies. Small and uncontrolled cohort studies inform thoracentesis and tube thoracostomy. Low quality evidence informs all other procedural-related bleeding risks.